2021
DOI: 10.1155/2021/2244202
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Model‐Based Weight‐Over Process Philosophy for Bridge Loading Capacity Evaluation and Rating Factor Estimation

Abstract: Existing rating methods estimate bridge loading capacity and demand from secondary actions due to live loads in the primary structural components. In these methods, uniaxial yielding stress is traditionally used to detect component capacity using either stress quantities or shear-moment actions to compute the capacity demand of the bridge. These approximations can lead to uncertainties in load capacity estimation. This article presents the weight-over process (WOP), a novel computer-aided approach to bridge lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Excellent examples of full-scale FE model updating based on field-measured and computed data were studied to modify the local element stiffness properties of structural members of existing bridges for evaluation and load rating [6][7][8][9][10][11]. Similarly, the historical dynamic and static behaviours of the existing bridge were investigated by the updated FE model, which confirmed that the design standards were applied to the load rating [12].…”
Section: Introductionmentioning
confidence: 72%
“…Excellent examples of full-scale FE model updating based on field-measured and computed data were studied to modify the local element stiffness properties of structural members of existing bridges for evaluation and load rating [6][7][8][9][10][11]. Similarly, the historical dynamic and static behaviours of the existing bridge were investigated by the updated FE model, which confirmed that the design standards were applied to the load rating [12].…”
Section: Introductionmentioning
confidence: 72%